Baseline parameters for rotational thromboelastometry (ROTEM®) in healthy pregnant Australian women: a comparison of labouring and non-labouring women at term. (February 2020) - Lee, J.; Wyssusek, K.H.; Kimble, R.M.N.; Way, M.; van Zundert, A.A.; Cohen, J.; Rowell, J.; Eley, V.A.
Highlights: Thromboelastometry compared for labouring vs non-labouring women. Measures of clot firmness were higher in labouring women than non-labouring women. Time to clotting onset was shorter in labouring women than non-labouring women. ROTEM® reference ranges in labouring women and non-labouring women were different. Greater hypercoagulability is seen in labouring compared to non-labouring women. Abstract: Background: Rotational thromboelastometry (ROTEM®) is a point-of-care coagulation test. Reference ranges in non-labouring women have recently been established from a cohort of women presenting for elective caesarean delivery using the recommended minimum sample size of 120. This study aimed to present baseline parameters for labouring and non-labouring women and to compare the mean values of these ROTEM® parameters. Methods: Ethical approval was granted for an opt-out recruitment approach for labouring women and written consent was obtained from non-labouring women (data published previously). ROTEM® testing was performed in these two cohorts at term gestation. Women with any condition affecting coagulation were excluded. ROTEM® Delta reference ranges were derived by calculating the 2.5 and 97.5 percentiles for INTEM/EXTEM/FIBTEM amplitude at 5 min (A5), coagulation time (CT), maximum clot firmness (MCF) and clot formation time (CFT). Results: One hundred and twenty-one labouring and 132 non-labouring women met inclusion criteria. The mean values for selected ROTEM® parameters for labouring and non-labouring women respectively were: FIBTEM A5, 21.05 and 19.7 mm ( P =0.008); EXTEM A5, 54.8 and 53.2 mm ( P =0.025); and EXTEM CT, 52.2 and 53.7 s ( P =0.049). Significant differences between the groups were observed in measures of clotting onset and clot firmness. Conclusions: We demonstrated a significant decrease in the mean time-to-clotting onset in labouring women compared with non-labouring women. Mean values for measures of clot firmness were greater in labouring women. In comparison to previously established ROTEM® baseline parameters for non-labouring women, this study provides evidence that there is greater hyper-coagulability in labouring women.